Analisis Yuridis Perizinan Lingkungan Berdasarkan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Muhammad Anwar Ibrahim; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Investment is one of the ways Indonesia can develop economic growth to realise a golden Indonesia by becoming the fifth largest economic power in the world. With that, Indonesia needs to regulate and make regulations that can facilitate investment by making the Job Creation Law. With the birth of the work copyright law by concocting, combining, deleting and changing several laws into one form of applicable law, namely omnibus law. Thus I conducted research through a normative juridical approach based on primary legal materials by using statutory materials and conceptual approaches by tracing legal materials using analytical study techniques and quantitative studies. From the results of the study found that the copyright law relating to environmental permits did not result in changes and is still relevant to the previous rules. Then the changes that occur only relate to environmental approval which is facilitated in order to simplify environmental licensing by integrating with the licensing system also strengthens the law indirectly.